The shaft friction degradation of piles under cyclic axial loading in wind turbine foundations. - Nardelli, Andrei (2019)
Onshore wind turbine foundations are mainly subjected to large overturning moments. The wind action imposes cyclic and dynamic loading conditions which occur in extreme and service scenarios. Deep foundations, when used, transfer this large overturning moment through a pile group which combines the axial and lateral resistance of all piles. Several authors noticed that cyclic axially loaded piles could have their resistance reduced due to shaft friction degradation. Considerable efforts have been made to understand this degradation phenomenon. However, the design and performance of cyclic axial loaded piles require greater advances. Therefore, this research sought to assess the shaft friction degradation of axially loaded piles in wind turbine deep foundations, especially for those located in Brazil. Several issues related to the main objective of this study had to be addressed because onshore wind turbine foundations are an area of recent research, especially in Brazil. The first stage of this research explored the key aspects of onshore wind turbine foundations in Brazil and compared them with the worldwide status. The main reason to explore this subject is that several authors consider onshore wind turbine foundations a well-understood topic; however, limited data from actual situations have been published, especially in developing countries where wind energy projects have recently started. Thus, a survey on Brazilian energy companies and foundation designers was conducted, and the first Brazilian database of wind turbine foundations was created. This database contains data from more than three thousand Brazilian wind turbine foundations. The key aspects, types and dimensions of these foundations were summarized. Worldwide, concrete gravity foundations are the most commonly used foundation type for onshore wind turbines. In Brazil, 43.3% of the wind turbines had shallow foundations, essentially concrete gravity, and 56.7% had deep foundations, mostly continuous flight auger piles. The foundation type was chosen according to the local foundation expertise and geotechnical conditions, which included soil type, water table level, soil layer resistance, the extent of porous soil layers and bedrock depth. This first stage of the research identified that Brazilian wind turbine foundations are significantly different from other countries. Approximately 70% of Brazilian wind turbine deep foundations used continuous flight auger piles, most of them embedded in sandy soils. Therefore, experimental investigations of the sand-concrete interface response under monotonic and cyclic loading are essential. The second and third stages of this research sought to investigate the sand-concrete interface response based on this recent insight. The second stage assessed the sand-concrete interface response through monotonic interface direct shear tests under different confinement conditions. The role of surface structural characteristics, confinement condition, sand mean diameter, particle morphology, sand gradation and relative density were evaluated. A nonlinear conceptual model of the interfacial-to-internal friction angle ratio was proposed according to normalized roughness and normalized waviness. Additionally, multiple regression was used to estimate the sand-concrete interface strength by the effect of constant normal stiffness. The results were essential to understand and to predict the sand-concrete interface response of concrete piles under static axial loading. The third stage explored the shaft friction degradation of cyclic axial loaded piles through sand-concrete and sand-steel cyclic interface direct shear tests. In geotechnical engineering practice, field and experimental tests are usually performed to evaluate the number of cycles until failure occurs under constant cyclic amplitude. According to this approach, cyclic failure can either occur quickly or not at all. From a practical viewpoint, the cyclic test times are unpredictable, which makes these tests difficult to plan and to perform. Therefore, a new approach based on increasing cyclic amplitude is proposed to overcome the conventional method. A simple cumulative damage model established a relationship between the cyclic loaded tests under constant and increasing cyclic amplitudes. The new approach provides additional insights into the cyclic interfacial response, such as the effect of previous cycles, the cyclic amplitude at failure and the displacement development throughout cycling. This new approach can be effortlessly extended to other experimental and field investigations. From a practical viewpoint, this new approach can reduce the cost and duration of projects. The author believes that this dissertation brought breakthroughs to the wind energy companies and to the geotechnical engineering community. However, further studies on onshore wind turbine foundations are still required.